NEED ANALYSIS FOR DEVELOPING ENGLISH LEARNING MODEL IN BANJARBARU SENIOR HIGH - Fadillah, Ridha; Saleh, Mursid (Universitas Negeri Semarang, 2013)
This explorative research aims to investigate the students’ English anxiety and the existing English learning model used by teachers as the baseline for the study to develop an effective English learning model. The method used in this research was a descriptive quantitative survey. The samples were 248 fifteen to nineteen year old students in second grade Banjarbaru senior high schools, South Kalimantan, Indonesia. The results indicated that the students’ English anxiety were at high level, including the three components of foreign language anxiety: communication apprehension, fear of negative evaluation, and test anxiety. In addition, the studentsexperienced anxious feeling in English classroom and English learning model used by English teachers were conventional model. It means that the teachers were as the center of learning